Ice-Prevention and De-Icing Capacity of Epoxy Resin Filled with Hybrid Carbon-Nanostructured Forms: Self-Heating by Joule Effect - Catalina Farcas; Oscar Galao; Luigi Vertuccio; Liberata Guadagno; M. Dolores Romero-Sánchez; Iluminada Rodríguez-Pastor; Pedro Garcés (Nanomaterials, 2021)
In this study, CNTs and graphite have been incorporated to provide electrical conductivity and self-heating capacity by Joule effect to an epoxy matrix. Additionally, both types of fillers, with different morphology, surface area and aspect ratio, were simultaneously incorporated (hybrid CNTs and graphite addition) into the same epoxy matrix to evaluate the effect of the self-heating capacity of carbon materials-based resins on de-icing and ice-prevention capacity. The self-heating capacity by Joule effect and the thermal conductivity of the differently filled epoxy resin were evaluated for heating applications at room temperature and at low temperatures for de-icing and ice-prevention applications. The results show that the higher aspect ratio of the CNTs determined the higher electrical conductivity of the epoxy resin compared to that of the epoxy resin filled with graphite, but the 2D morphology of graphite produced the higher thermal conductivity of the filled epoxy resin. The presence of graphite enhanced the thermal stability of the filled epoxy resin, helping avoid its deformation produced by the softening of the epoxy resin (the higher the thermal conductivity, the higher the heat dissipation), but did not contribute to the self-heating by Joule effect. On the other hand, the feasibility of electrically conductive epoxy resins for de-icing and ice-prevention applications by Joule effect was demonstrated.